Enhanced Microwave Absorbing Characteristics of Cerium Barium Ferrite Composite: Effect of Sintering Temperature Variation - Widanarto, Wahyu; Tamtowi, Tomy; Effendi, Mukhtar; Rahmawati, Dina; Supriyanti, Retno; Ghoshal, Sib Krishna; Kurniawan, Candra; Jatmika, Jumaeda; Handoko, Erfan; Umar, Lazuardi; Alaydrus, Mudrik (Molekul, 2025)
ABSTRACT. Cerium barium ferrite composites (CeBFCs) with improved microwave absorbance in the X-band spectral region are advantageous for varied advanced applications. Thus, the influence of various sintering temperatures on the microwave-absorbing traits of CeBFCs was evaluated. The main objective was to enhance the selective microwave absorption of BFC by modifying its magnetic properties through the substitution of Fe³⁺ with Ce³⁺ in the lattice structures. Four composites of CeBF were synthesized via mechanical alloying and sintered at 600, 800, 1000, and 1100°C. The produced samples were analyzed using XRD, VSM, and VNA to determine their microstructures, magnetic properties, and microwave reflection loss at X-band frequencies. XRD results revealed a significant promotion in forming a more pure crystalline barium hexaferrite phase at sintering temperatures higher than 800°C. This structural enhancement could directly influence the magnetic properties of the specimens with a progressive increase in the saturation magnetization with rising sintering temperature. In addition, the sintering temperature variation effectively modulated the electromagnetic properties (complex relative permeability and permittivity) that are vital for impedance matching and optimal wave absorption. The composite sintered at 1000°C displayed an optimal microwave absorption, indicating the lowest reflection loss within the X-band. The obtained products were shown to attenuate and dissipate surplus electromagnetic energy within the 8-12 GHz frequency range. The observed superior performance of the composites was ascribed to a balanced interplay between the magnetic and dielectric losses, leading to efficient impedance matching. It was affirmed that careful tuning of the sintering temperature can improve the crystalline phases, magnetic, electromagnetic, and microwave absorption properties of the proposed CeBFCs. Keywords: Cerium barium ferrite, Microwave absorption, Reflection loss, Sintering temperature, X-band